Metal Oxide Nanomaterials for the Photodegradation of Phenol. (12th April 2016) - Zhan, Huiying; Jiang, Yufeng
ABSTRACT: The decomposition of phenol by four metal oxide nanomaterials was investigated by adsorption and photocatalytic degradation. The results from adsorption experiments were fit to a Langmuir model. The theoretical monolayer adsorption capacities for nano-TiO2, -Al2 O3, -ZnO, and -CuO were approximately 14.35, 14.28, 13.72, and 5.29 mg/g, respectively. Nano-TiO2 and -CuO had the largest Langmuir model coefficients: both were 0.0324 L/mg. The adsorption capacity of phenol was higher in basic conditions than in acidic solution. Photodegradation was characterized by pseudo-first-order models. The total removal rates for nano-TiO2, -Al2 O3, -ZnO, and -CuO after 3 hours of irradiation were 89.0%, 70.8%, 57.3%, and 61.6%, respectively. The differences between phenol and total organic carbon concentrations for nano-TiO2, -Al2 O3, -ZnO, and -CuO were 42.92%, 20.11%, 8.29%, and 16.78%, respectively. Nano-TiO2 provided the maximum capacity for photodegradation and produced the most intermediates. The majority of the phenol was degraded to resorcinol and hydroquinone as intermediates to acetic acid.